If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26x=x+50
We move all terms to the left:
26x-(x+50)=0
We get rid of parentheses
26x-x-50=0
We add all the numbers together, and all the variables
25x-50=0
We move all terms containing x to the left, all other terms to the right
25x=50
x=50/25
x=2
| 5x+5=3x+13=180 | | 18f=10f+64 | | 5x+5=3x+73=180 | | 3f+6=f-2 | | -m+-5=0 | | 11=t4+ 7 | | 12-f3=12-3 | | K=8+2t | | 11x=8-3(6-2x) | | k3− 10=-8 | | 5p+2=12-5p | | 2z+-2=8 | | 10=1+3q | | 2=2b-6 | | 1x=1.6 | | 0.9y=12.5 | | x-0.06*x=184510 | | 7x+49=2x+94=180 | | 6x+24x+9=0 | | -3+0.25x=-4 | | 3(3x+3)+5x+1=26 | | 6=2s=10 | | -2(-5x-4+x+1=119 | | (a+2)^2+a^2=10^2 | | 9x=1440 | | (a+2)a=10^2 | | 4x+1/5(8x+6)=2(4x+3 | | 4a+3=a+18 | | p/100=3/20 | | 5x-20=8x+2 | | (5x-3)=(6x-8) | | (s+4)^2=196 |